Studying the expression of productivity and immunity genes of chickens under the influence of feed glyphosate using the RNA-seq method - Laptev G. Yu.; Yildirim E. A.; Ilina L. A.; Tyurina D. G.; Ponomareva E. S. (BIO Web of Conferences, 2023)
The aim of the study was to study the effect of different concentrations of glyphosate on meat productivity and differential expression of genes for immunity and broiler productivity. Broilers were divided into groups: Control I, who received a diet without the introduction of glyphosate, Experimental II, who received a diet with the addition of glyphosate at a dose of 10 mg/kg of feed (0.5 MPC for food); Experimental III, who received a diet with the addition of glyphosate at a dose of 20 mg/kg of feed (1 MPC); Experimental IV, who received a diet with the addition of glyphosate at a dose of 100 mg/kg of feed (5 MPC). Transcriptome analysis was performed by RNA-seq on the Illumina Miseq platform, using the TruSeq Stranded mRNA kit (Illumina, USA). In the 22-28-day period of broiler rearing, a decrease in live weight gain (83 g less) was observed in Experimental group III compared to Control I (P≤0.05). It has been shown that glyphosate at the level of 1 and 5 MPC for food causes activation (P≤0.05) of the proinflammatory response genes (IL15, IL1B, IL34, IL22) and apoptosis (Casp1, Casp2, Casp6, Casp7, Casp8, Casp9) up to 31.1 times, which probably leads to the redistribution of nutrients in in the body towards the immune system, reducing the functions of absorption in the intestine. In parallel, there is an inhibition (P≤0.05) of the expression of genes that have a direct effect on growth and development, which ultimately leads to a decrease in poultry meat productivity. Exposure to glyphosate is an important but unaccounted-for risk factor for reducing meat productivity in birds, acting through a change in gene expression.